Teachers Perspective of Using English as a Medium of Instruction in Mathematics and Science Subjects - Mansor, Norudin; Badarudin, Mohamed Ishak; Mat, Azman Che (2011)
The policy of changing the medium of instruction in the teaching of mathematics and science from Bahasa Melayu to English is an important innovation affecting teachers of mathematics and science. It poses special challenges not only for teachers who have been trained in the Malay medium but also for those trained in English. This investigation seeks to find out the achievement of students in mathematic and science subjects after considering the impact of prominent independent variables such as, the school, class and home environment, the teaching methodology and the teachers' attitude. Analysis of the development in the state of Terengganu has been carried out by the distribution of questionnaires to teachers involved. Result of the correlation and multiple regressions indicated that all the three factors are significantly associated towards students' achievement. However, the teaching methodology indicated a low level of moderate correlation which is believed to be the immediate issue that needed to be addressed in the new system. (Contains 3 tables and 1 figure.)